Managing precarity at the intersection of individual and collective life: A Membership Categorisation Analysis of Tensions and Conflict in Identities within an Online Biosocial Community. (January 2023) - Cheded, Mohammed; Curry, Niall; Gilchrist, Alan; Hopkinson, Gillian
This paper explores how individuals living within high-stakes precarious categories navigate their identity within online spaces. Using Membership Categorisation Analysis, we investigate how categorical inferences are indexed by those individuals within online biosocial communities in everyday speech, as part of their construction of identities. More specifically, we analyse online interactions of women who have been identified as carrying a BRCA gene mutation in an online biosocial community. Our findings show how (1) the online spaces participate in constituting and sustaining a form of collective responsibility, where those who are within a high-stakes precarious identity category are expected to not only support and educate each other, but also monitor the compliance to category predicates, and (2) the tensions and conflict in making sense of, belonging to, resisting and sustaining a category membership often occur when there are clashes with the socio-moral order. Overall, this paper's contributions are twofold, first, methodologically, the use of Membership Categorisation Analysis provides an insightful analytic approach to identities, online communities and their organisation. Second, the emerging tensions identified provide insight into the complex ways in which online communities offer a forum in managing precarious identity as individual and collective life intersect.